2011
DOI: 10.1037/a0022616
|View full text |Cite
|
Sign up to set email alerts
|

Detecting intimate partner violence in family and divorce mediation: A randomized trial of intimate partner violence screening.

Abstract: Handling mediation cases with a history of intimate partner violence (IPV) is one of the most controversial issues in the field of divorce mediation. Before deciding whether and how to mediate cases with IPV, mediators must first detect violence. Using random assignment of cases to an enhanced screening condition (n ϭ 30) and to a standard screening control condition (n ϭ 31), we compared information gathered from a brief, behaviorally specific IPV screening questionnaire to mediators' independent determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
6
40
0
Order By: Relevance
“…We do have data on this issue. Specifically, in a study (Ballard, Holtzworth‐Munroe, Applegate, & Beck, 2011) using data from the same clinic and time period and using the same method to detect IPV as the present study, we found that families who had experienced IPV were significantly less likely to reach a mediation agreement than families without a history of IPV (42% of families with a history of IPV versus 16% of families without a history of IPV). In sum, the present study is limited to cases that were referred to mediation by judges, not screened out of mediation by mediators who reached agreement.…”
supporting
confidence: 55%
“…We do have data on this issue. Specifically, in a study (Ballard, Holtzworth‐Munroe, Applegate, & Beck, 2011) using data from the same clinic and time period and using the same method to detect IPV as the present study, we found that families who had experienced IPV were significantly less likely to reach a mediation agreement than families without a history of IPV (42% of families with a history of IPV versus 16% of families without a history of IPV). In sum, the present study is limited to cases that were referred to mediation by judges, not screened out of mediation by mediators who reached agreement.…”
supporting
confidence: 55%
“…However, the sample of current study participants is relatively large and recruited from a demographically diverse metropolitan location. Also, the current study findings are consistent with those gathered in a very different mediation clinic setting (i.e., law students in southern Indiana) in the only previous randomized controlled trial comparing different IPV screens (Ballard et al, 2011). We recommend that researchers continue to examine the decision-making process of mediators or mediation staff; ideally, however, recommendation to mediation would be based on empirical data regarding the outcomes of cases with a history of IPV in mediation.…”
Section: Discussionsupporting
confidence: 83%
“…Following Wolchik et al () and Ballard, Holtzworth‐Munroe, and Applegate (), a MR control group intervention was created. Reading assigned for both groups was Because It's for the Kids (McIntosh, ), a 20‐page booklet covering a spectrum of divorce/conflict/communication‐specific information for parents, concerning children from 0–18 years.…”
Section: Methodsmentioning
confidence: 99%